Shoppers and how they travel. - (:unkn) unknown (My University, 2006)
Sustrans conducted a study on two neighbourhood streets in Bristol to find out what retailers think what kind of transport mode their customers prefer. The results show an obviously overestimation of the importance of cars by retailers and how much their customers are consuming in general.
Keywords: Individualverkehr; Fahrradverkehr; Befragung; Erhebung; Statistik; Verkehrsmittelwahl; Fahrradnutzung; Mobilitätsverhalten; Einkaufsverhalten; Wegezweck